PENENTUAN DALAM PENETAPAN DOSEN TETAP MENGGUNAKAN METODE WEIGHTED PRODUCT DI AMIK POLIBISNIS PERDAGANGAN - Zulkhairani Zulkhairani; Lia Umbari Putri; Hidayatullah Hidayatullah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract : : Lecturers are the most important part and the front gate in educating students so that lecturers with good skills are needed, lecturers are a profession that requires expertise and sufficient technical knowledge to support their professionalism in advancing a campus. In the appointment of lecturers, it can still be seen from the active involvement of a lecturer in conducting Tri Dharma Perguruan Tinggi activities, both in terms of education and teaching, research and community service, therefore special attention is needed in assessing the appointment of permanent lecturers supported by the Weighted Product method. The purpose of this study is to improve the quality of the lecturers received. The results of this research are in the form of a Decision Support System (SPK) to determine permanent lecturers at private universities, this research has been able to make a decision support system application and apply the Weighted Product method as a solution to the problem of determining permanent lecturers at private universities where test results are obtained the accuracy of applying the Weighted Product method in determining permanent lecturer candidates by 80%. Keywords : Lecturer, Profession, SPK, Weigthed Product, System Abstrak :Dosen merupakan bagian terpenting dan gerbang terdepan dalam mendidik mahasiswa sehingga dibutuhkan dosen dengan kemampuan yang baik, dosen merupakan sebuah profesi yang membutuhkan keahlian dan pengetahuan teknis yang cukup untuk menunjang profesionalismenya dalam memajukan sebuah kampus. Dalam pengangkatan dosen tetap dilihat dari aktifnya seorang dosen dalam melakukan kegiatan Tri Dharma Perguruan Tinggi, baik dari segi pendidikan dan pengajaran, penelitian maupun pengabdian kepada masyarakat, oleh karena itu perlu perhatian khusus dalam menilai pengangkatan dosen tetap dengan didukung  metode Weighted Product. Tujuan dari penelitian ini adalah untuk meningkatkan kwalitas dosen yang diterima. Hasil dari penelitan ini adalah berupa Sistem Pendukung Keputusan (SPK) untuk untuk menentukan dosen tetap di perguruan tinggi swasta,  penelitian ini telah mampu membuat aplikasi sistem pendukung keputusan dan menerapkan metode Weighted Product sebagai pemecahan masalah penentuan dosen tetap pada perguruan tinggi swasta dimana hasil pengujian diperoleh akurasi penerapan metode Weighted Product dalam menentukan calon dosen tetap sebesar 80%. Kata kunci : Dosen, Profesi, SPK, Weigthed Product, Sistem